Gender issues and livelihood pattern of migrant women labourers of farm families - PONNUSAMY, K; SENDHIL, R (The Indian Journal of Agricultural Sciences, 2015)
Migration of labour is getting feminized especially in the developing countries like India in the recent past, and more so in Odisha state that face acute migration where farm women migrate for a better livelihood option. In the milieu, the present study was carried out to document the gender issues and livelihood pattern of migrant women labourers of farm families from Odisha. The study sourced data from a survey conducted in the labour congregating areas of Bhubaneswar during 2011-12. Highest percentage of women labour migrants were within the age group of 26-35 (40%) and lowest number was found within 56-65 age group (4%). Ninety two per cent of the respondents were wage labourers and among them, a majority (52%) of women performed both construction and road work, and 40% performed only construction work. A majority of the respondents (42%) earned a monthly income ranging from rs.` 2 000 to `rs. 3 000 and their total monthly family income varied from `rs. 5 000 to `rs. 8 000. However, 68% of the respondents saved their income for the future requirements and 32% of the respondents were living hand-to-mouth life due to a large family size. The income of majority of respondents ranged from rs.` 2 000 to rs.` 3 000 per month and their family income was also within the range of rs. 2 000 to rs.` 8 000. Moreover, a meager amount of money was sent to the family at origin which is not even sufficient to purchase cereals and pulses. The study concludes that, adoption of effective and efficient region specific strategies through entrepreneurial skills coupled with some profitable agricultural business ventures will curtail the rate of rural migration.